Marketing Strategy Model for Building Customer Loyalty in Feed Wholesale Business - Saetang, Wichitra; Pathomsirikul, Yaowapa (The Journal of Behavioral Science, 2016)
This research was aimed at developing a marketing strategy model for building loyalty among customers in the animal feed business sector of Thailand. The factors which relate to customer loyalty in this sector were the feed wholesaler executive’s interpersonal relations, organization, the environments and the marketing strategy. The instrument used in this quantitative research was a questionnaire which had been tested and qualified for reliability and content validity. Stratified and random sampling methods were used to collect the data from 700 feed retailers in Thailand. The obtained data was analyzed using descriptive statistics, path analysis, and structural equation modeling (SEM). The results from testing the marketing strategy model for building customer loyalty in the feed wholesale business (MCL) indicated that the organization had the highest impact on customer loyalty among feed retailers, while interpersonal relations had the highest impact on customer loyalty among feed retailers mediated by the marketing strategy of feed wholesalers. The components of marketing strategy in order of importance from highest to lowest were product strategy, distribution, marketing communication, customer relationship management and pricing. Furthermore, the marketing strategy had an impact on customer loyalty among feed retailers in Thailand showing that repeat purchase was the highest. The MCL model was well consistent with the empirical data at the significant level 0.05 (c2=219.93, df=159, c2/df=1.38, p-value=0.00099, RMSEA =0.023, GFI=0.97, and AGFI =0.95). Keywords: interpersonal relations, marketing strategy, customer loyalty, feed wholesalers, feed retailers, feed wholesale business